2016
DOI: 10.1088/0957-4484/27/50/505602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optoelectronic properties of quaternary GaInAsSb alloy nanosheets

Abstract: Quasi-one-dimensional (1D) nanostructures have been extensively explored for electronic and optoelectronic devices on account of their unique morphologies and versatile physical properties. Here, we report the successful synthesis of GaInAsSb alloy nanosheets by a simple chemical vapor deposition method. The grown GaInAsSb alloy nanosheets are pure zinc-blende single crystals, which show nanosize-induced extraordinary optoelectronic properties as compared with bulk materials. μ-Raman spectra exhibit a multi-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Since the studies of heterostructures between 2D layered materials showed promising applications in various fields, group III-V and II-VI non-layered semiconductors with distinct properties were also incorporated into TMDs materials and formed new kind heterostructures to realize novel functionality [10][11][12][13]. For example, CdS/MoS 2 [14], PbS/MoS 2 [15] and GaN/WSe 2 [16] vertical heterostructures have been prepared with exotic performances compared with single TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the studies of heterostructures between 2D layered materials showed promising applications in various fields, group III-V and II-VI non-layered semiconductors with distinct properties were also incorporated into TMDs materials and formed new kind heterostructures to realize novel functionality [10][11][12][13]. For example, CdS/MoS 2 [14], PbS/MoS 2 [15] and GaN/WSe 2 [16] vertical heterostructures have been prepared with exotic performances compared with single TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…When the incident light intensity is 10 mW/cm 2 , the obtained R for this PD is 158 A/W and the EQE can reach to 2.0 × 10 4 %, both of which are higher than those reported for GaInAsSb thin-film PDs [24] and are comparable with other previously reported single-nanostructured PDs. [36,37] The high R and EQE of the representative PD can be explained with two factors. Firstly, the large surface-tovolume ratio of the nanowires can easily induce the hole-trap states at the nanowire surface, and these trap states can somehow increase the photocurrent density effectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with binary and ternary solid‐solutions, quaternary semiconductor solid‐solution exhibits some unexpected properties valuable for technological applications in diverse fields. So far, the quaternary semiconductor solid‐solutions have been reported for groups (II–VI)–(II–VI), (III–V)–(III–V), and (II–VI)–(III–V) material systems, which mainly include ZnCdSSe, ZnCdSeTe, GaInAsSb, GaN‐ZnO, GaP‐ZnS, GaP‐ZnSe, and GaAs‐ZnSe …”
Section: Classification Of Semiconductor Solid‐solution Nanostructuresmentioning
confidence: 99%
“…The CVD method is especially effective to synthesize quaternary solid‐solution nanostructures made of two different binary compounds. For example, Pan and co‐workers has demonstrated the successful synthesis of a variety of quaternary solid‐solution nanostructures such as GaInAsSb, GaZnSeAs, and ZnCdSSe using this method, in which the binary compound precursors are isolated in two separated transport channels and are transported to the reaction zone at the same time (Figure b). Using similar method, we have also fabricated GaP‐ZnS, GaP‐ZnSe, and GaN‐ZnO solid‐solution nanowires with variable sizes and tunable optoelectronic properties.…”
Section: Synthetic Strategies Of Semiconductor Solid‐solutionsmentioning
confidence: 99%